PSC subtyping based on TTF‐1 and p40 expression reveals distinct molecular characteristics and therapeutic strategies. Issue 5 (8th June 2022) - Yang, Zhenlin; Tian, He; Li, Lin; Li, Chao; Xu, Jiachen; Bie, Fenglong; Chen, Ying; Tian, Yanhua; Bai, Guangyu; Peng, Yue; Yang, Junhui; Fan, Tao; et al.
Abstract: Pulmonary sarcomatoid carcinoma (PSC) is a unique form of poorly differentiated nonsmall cell lung cancer (NSCLC) and is notorious for its highly malignant nature and dismal prognosis. To introduce effective treatment for PSC patients, precise subtyping of PSC is demanding. In our study, TTF‐1 and P40 immunohistochemistry (IHC) staining were applied to 56 PSC patients with multiomics data. According to IHC results, we categorized these patients into three subgroups and profiled their molecular contexture using bioinformatic skills. IHC results classified these patients into three subgroups: TTF‐1 positive subgroup (n = 27), P40 positive subgroup (n = 15) and double‐negative subgroup (n = 14). Spindle cell samples accounted for 35.71% (5/14) of double‐negative patients, higher than others ( P  = .034). The three subgroups were heterogeneous in the genomic alteration spectrum, showing significant differences in the RTK/RAS pathway ( P  = .004) and the cell cycle pathway ( P  = .030). The methylation profile of the double‐negative subgroup was between the other two subgroups. In similarity analysis, the TTF‐1 and p40 subgroups were closely related to LUAD and LUSC, respectively. The TTF‐1 positive subgroup had the highest leukocyte fraction (LF) among several cancer types, and the tumor mutation burden (TMB) of the p40 positive subgroup ranked third in the TMB list, suggesting the applicability of immunotherapy for PSC. The study established a new subtyping method of PSC based on IHC results and reveals three subgroups with distinct molecular features, providing evidence for refined stratification in the treatment of PSC. Abstract : What's new? Although several studies have highlighted the genomic features of pulmonary sarcomatoid carcinoma, no widely accepted subtyping strategy has been introduced so far, hampering effective treatment. Our study is the first to subtype this rare and highly malignant tumor based on immunohistochemistry staining for TTF‐1 and p40. The authors accordingly characterized the molecular features of three pulmonary sarcomatoid carcinoma subgroups using whole‐exome sequencing and methylome profiling. Our study helps establish a new, more affordable subtyping method for pulmonary sarcomatoid carcinoma than genetic subtyping and provides evidence for a refined stratification of patients towards treatments.